PEMBINAAN PENGELOLAAN PEMBELAJARAN BERBASIS KURIKULUM NASIONAL BAGI GURU - Naskah, Naskah; Rohani, Rohani; Afrida, Afrida; Faruq, Umar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This community service is in the form of coaching on national curriculum-based learning management for Al-Faruqi Kampar Islamic boarding school teachers. The purpose of this coaching is to be able to develop components of curriculum content material according to consumption by students at a certain level of ability. The coaching approach used is participatory action research (PAR), the PAR cycle includes 4 stages for each cycle, namely planning (Plan action), action (Take Action), observation (observe) and Reflection (Reflection). This community service activity was carried out with the school, namely the Al-Faruqi Islamic boarding school and after that brought in resource persons who were experts in the field of National-based curriculum development. The methods used were Presentation and Practice, Demonstration, and Evaluation Design. The results of coaching on national curriculum-based learning management for Al-Faruqi Kampar Islamic boarding school teachers showed that the participants who came understood what had been conveyed by the speakers and the teachers were able to design and implement learning modules that were the principles of the independent curriculum, and would continue to try to carry out PBM according to existing conditions and curriculum.